Pengaruh Kemudahan Data, Fitur Layanan Dan Kepercayaan Customer Terhadap Minat Penggunaan E-Wallet Pada Aplikasi Dana - Moniq Angelia Cahya Kartika; Tri Ratna Pamikatsih (CV. Aksara Global Akademia, 2023)
Technological advances in Indonesia are so rapidly developing in human life that it cannot be separated from the use of technology in the midst of global competitors. In the increase in cashless e-wallet transactions for online payments, its application has increased dramatically around the world. DANA introduces its users to payments through digital wallets and non-cash and non-card transactions, making it easier for users. The DANA digital wallet concept is different from other digital wallets that are already present in the Indonesian market, namely with the open platform concept. This study aims to determine the effect of data convenience, service features, and customer trust on asking to use e-wallets in the DANA application. The population in this study were all e-wallet users in East Java. The data collection technique used a questionnaire. Data analysis in the form of multiple linear regression analysis. Partial test results obtained Ease of Data does not have a significant effect on Interest in Using e-wallets in the DANA application. Partial test results obtained Service Features and Customer Trust have a significant effect on Interest in Using e-wallets in the DANA application. Comprehensive results obtained Ease of Data, Service Features, and Trust have a simultaneous effect on Interest in Use.